(untitled) (Revista Rupturas, 2015)
The present essay makes an analysis of the curricular reforms implemented in Costa Rica in the period between 2006 and 2014, under the premise that these answer to the establishment of the Social Democrat Educational Model, which was active in the country between 1957 and 1985. To perform this analysis, a definition is built from the critical curriculum that frames the creation process of a new interpretation of the periods that Integrate the educational history post-independence so that, afterwards, there is an analysis of the Social Democrat Educational Model features and the Neoliberal Pedagogical Adjustment, to finally enquire on the implemented reforms in the period under study and discuss the implications of the premise developed in the essay for the progressive sectors of the educational system.